The efficiency of Color Models layers at Color Images as Cover in text hiding - Qasim Mohammed Hussein; Ahmed Saadi Abdullah; Nada Qasim Mohammed (Tikrit Journal of Pure Science, 2023)
The color images are used widely as a cover in hiding of the information. Since the variety of applications of the color image there are several color models of color image. Most color models consist of three layers.  The nature of the color mode of the cover plays a main role in determining the robustness and security of hiding algorithm.